Conventional and new proposals of GnRH therapy for ovarian, breast, and prostatic cancers - Garrido, Maritza P.; Hernandez, Andrea; Vega, Margarita; Araya, Eyleen; Romero, Carmen (Frontiers in Endocrinology, 2023)
For many years, luteinizing hormone-releasing hormone or gonadotropin-releasing hormone (GnRH) analogs have been used to treat androgen or estrogen-dependent tumors. However, emerging evidence shows that the GnRH receptor (GnRH-R) is overexpressed in several cancer cells, including ovarian, endometrial, and prostate cancer cells, suggesting that GnRH analogs could exert direct antitumoral actions in tumoral tissues that express GnRH-R. Another recent approach based on this knowledge was the use of GnRH peptides for developing specific targeted therapies, improving the delivery and accumulation of drugs in tumoral cells, and decreasing most side effects of current treatments. In this review, we discuss the conventional uses of GnRH analogs, together with the recent advances in GnRH-based drug delivery for ovarian, breast, and prostatic cancer cells.